Barriers and enablers to diabetic retinopathy screening uptake: a systematic literature review - Anaya Geoffrey Kesesi; Khisa Allan Wanjala; Marera Dominic; Mabonga Cyprian (International Journal Of Community Medicine And Public Health, 2026)
Diabetes mellitus is a growing worldwide health concern with fast-rising prevalence and serious health complications. Early detection through routine Diabetic retinopathy screening is effective in preventing vision loss. Objective: The study sought to identify factors that hinder and promote uptake of diabetic retinopathy screening. This study followed PRISMA to conduct and report findings. Relevant literature was identified; data were extracted, summarized in a table and analyzed. References were cited using EndNote. Diabetic retinopathy screening uptake in low- and middle-income countries, especially in sub-Saharan Africa, was consistently low. Studies from Malawi, and Kenya reported screening rates ranging from 10.5% to 25.6%, with annual uptake between 13.3% and 20%. This demonstrates a substantial gap between recommended screening guidelines and actual practice. Knowledge of Diabetic retinopathy screening services by patients and referral by healthcare workers were the strongest predictors of screening uptake. In Kenya, higher education level, family history of diabetes and provider referral were associated with increased screening utilization. Worldwide evidence reveals marked inequities in DR screening adherence, with higher uptake in developed countries at around 66% compared to less developed ones at approximately 39%. Europe observed the highest adherence to screening at 81.3%. Studies indicate that diabetic retinopathy screening uptake remains suboptimal, highlighting the need for integrated diabetes and eye care services, provider-initiated referrals, and enhanced patient awareness to improve screening coverage. The role of data management systems in DR screening reporting, monitoring, and evaluation remains underexplored in many studies.